Portrait photograph of an unidentified child, possibly female (Natick, MA) - Thayer, Alexander Wheelock, 1817-1897 (previous owner):::Collector::::::::::::; Randall Bros. (photographer):::Photographer:::::::::::: (United States; Randall Bros.; Natick, MA, 2023)
Mezzotint portrait photograph of an unidentified child, possibly female (undated) by Randall Bros., Natick, MA, from the personal collection of Alexander Wheelock Thayer.